MEMBENTUK BUDAYA ORGANISASI DI LINGKUNGAN LEMBAGA PENDIDIKAN ISLAM - Arfandi Arfandi; Ukhtul Iffah (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2019)
Organizational culture is the shared values and beliefs that underlying organizational identity. That is an invisible social force that can move people in organization to carry out work activities. Persons in organization learns the culture unconsciously that applies within an organization. Culture is also the main determinant of someone’s wishes and behaviours. Human behaviors are usually influenced by the surrounding environment, so that the values, perceptions, preferences, and behaviors between persons who live in a certain environment can be different from other peoples in other environments. Culture encompasses all knowledges, beliefs, skills, arts, morals, laws, customs, and human habits, as members of society. Culture that consists of ideas, attitudes, values and habits of individuals are learned from their lives in the social environment.